DAMPAK HANDPHONE PADA SISWA DI SMA NEGERI 1 HARAU - Dona Despika Susanti; Fadhilla Yusri (Pusat Riset dan Inovasi Nasional, 2023)
Mobile is a long-distance communication tool that is in the form of a mini and can be carried anywhere. Mobile is very much useful if we can use it properly. If we misuse it, the negative impact will be much more that will occur. Mobile in this modern era is like a staple food for every group, especially students. The purpose of this study was to see the impact of mobile applications on student behavior at SMA 1 Harau. This study uses a qualitative descriptive approach, namely a study with field observations, then describes the data that has been analyzed to draw conclusions. Collecting data by way of observation and interviews. The results of the study show that students spend more time with mobile phones than other useful activities, causing students to become addicted to mobile phones. Excessive use of mobile phones has negative impacts such as starting to become addicted to the internet, games, and so on. Most students feel preoccupied with games on their cellphones compared to interacting with their friends in the real world. Often by holding a cellphone, sometimes there are students who don't listen to the words of their parents and some are even angry with their parents when talking to them. The positive side of using a cellphone is very much if we are smart at operating cellphone applications properly. With mobile phones we can communicate long distances, can be used for entertainment when we are bored, add friends, find out information faster, and so on.